(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The kinetic study was carried out to determine the iron content in the ashed cow blood extract. The cow blood was subjected to pretreatment process such as boiling, heating, drying, grinding and ashing. The ashed cow blood was digested in distilled water for 24 hours and then filtered. Few drops of chromic acid was added to the filtrate and left to equilibrate. This was necessary to release iron from the coordinated blood extract. The iron content of the filtered extract was determined spectrophotetrically, using AAS and a concentration of 1.9200 mg/litre of iron was recorded. Kinetic studies were carried out by introducing equal volume of local ethanol into the filtrate and the iron concentration was monitored using AAS at 10 minutes interval. The ethanol led to a gradual decrease of the concentration of iron with increase in time. The average pH of the reaction mixture was 7.5 which was slightly alkaline or near neutral. Other kinetic parameters such as rate of reaction, rate constants, order of reaction, half life and full-life of the kinetics of the effect of ethanol on iron content of the ashed cow blood were determined. The rate of reaction obtained was 0.0215 mg/litre/minute. The rate constant value obtained was 0.010025 mg-dm3min-1. The kinetics revealed a second order type as it was found to fit the second order integrated rate law. A half life value of 51.95 minutes was determined which corresponded to a full life of 103.90 minutes. Discussions are made based on the dangers of alcohol intake to the iron contents of the body.